Ancaman Siber terhadap Infrastruktur Kritis Indonesia: Analisis Kebijakan Keamanan Nasional di Era Digital - Jihan Aqilah Idris Sadik (Madani: Jurnal Ilmiah Multidisiplin, 2026)
As the digital era continues to advance rapidly, critical infrastructure in Indonesia, particularly in the energy, telecommunications, and financial sectors, has become increasingly vulnerable to cyberattacks. Various cyber threats, including ransomware, Distributed Denial of Service (DDoS) attacks, and state-sponsored cyber espionage, are growing in frequency and sophistication. This study aims to examine the effectiveness of Indonesia’s national cybersecurity policies, specifically Government Regulation No. 42 of 2023 concerning the National Cybersecurity Strategy and Law No. 11 of 2008 concerning Electronic Information and Transactions. The research employs a qualitative approach through policy document analysis and case studies of major cyberattacks, including the WannaCry attack in 2017 and the attack on PLN in 2022. The findings indicate that existing policies continue to face several challenges, such as weak inter-agency coordination, a shortage of cybersecurity professionals, and the suboptimal utilization of Artificial Intelligence (AI) technologies for early threat detection. Therefore, policy reforms are needed to emphasize a risk-based approach, strengthen public-private partnerships, and enhance public awareness of cybersecurity issues.